Criminal law and precrime : legal studies in Canadian punishment and surveillance in anticipation of Criminal guilt /: legal studies in Canadian punishment and surveillance in anticipation of Criminal guilt. (2017) - Jochelson, Richard, 1973-; Gacek, James; Menzie, Lauren; Kramar, Kirsten Johnson, 1965-
No abstract available